Global diversity, population stratification, and selection of human copy number variation - Sudmant, Peter H. (2015)
In order to explore the diversity and selective signatures of duplication and deletion human copy number variants (CNVs), we sequenced 236 individuals from 125 distinct human populations. We observed that duplications exhibit fundamentally different population genetic and selective signatures than deletions and are more likely to be stratified between human populations. Through reconstruction of the ancestral human genome, we identify megabases of DNA lost in different human lineages and pinpoint large duplications that introgressed from the extinct Denisova lineage now found at high frequency exclusively in Oceanic populations. We find that the proportion of CNV base pairs to single nucleotide variant base pairs is greater among non-Africans than it is among African populations but we conclude that this difference is likely due to unique aspects of non-African population history as opposed to differences in CNV load.